146k views
2 votes
F(x) = (x - 1)(x + 2)(x+3)

User Dlitwak
by
5.9k points

2 Answers

3 votes

Answer:

f(x) = (x^3 + 4x^2 + x - 6)

Explanation:

f(x) = (x-1)(x+2)(x+3)

Start with two polynomials

(x-1)(x+2) = (x^2+2x-x-2) = (x^2+x-2)

Multiply that result by the remaining binomial

(x^2 + x - 2)(x + 3) = (x^3 + 3x^2 + x^2 + 3x - 2x -6) = (x^3 + 4x^2 + x - 6)

User Finn
by
4.6k points
0 votes

Answer:

f(x)=(x-2)(x+1)(x+3). f(x)=(x−2)(x+1)(x+3) f ( x ) = ( x - 2 ) ( x + 1 ) ( x + 3 ). Find the point at x=−2 x = - 2

Explanation:

i think. tbh i dont really know

User Relliv
by
4.7k points